THE IMPACT OF PRICE AND PRODUCT QUALITY ON CUSTOMER LOYALTY (A Study on Customers of Tempeh Chips Rohani in Purwantoro Village, Blimbing District, Malang City) - Faris, Maksum; Nuringwahyu, Sri; Hardati, Ratna Niken (Transpublika Publisher, 2023)
The main objective of this study was to analyze how the price and quality of products influence customer loyalty within the customer base of Rohani tempe chips in the local community of Purwantoro Village, located in the Blimbing District of Malang City. In order to achieve this goal, an explanatory research approach was chosen to delve into the intricate connections between these variables and understand how they interact with each other. Primary data was gathered for this research by distributing Likert scale questionnaires to individuals who regularly purchase Rohani tempe chips. The sample size for the study was determined using Malhotra's formula, resulting in a total of 100 respondents participating in the survey. The outcomes of the study indicated that both the price and quality of the product had a significant influence on customer loyalty, whether considered together or individually.